Bacillus subtilis sp. B1, Chitinase Producing Isolated from Indonesian Tropical Shrimp Pond Waste Water - Prasetyo, Amrih; Nurnawati, Elisa (Proceeding International Conference on Science and Engineering, 2017)
Twenty-five bacterial strains isolated from shrimp farming ponds were screened for their growth activity on chitin as the sole carbon source. The highly chitinolytic bacterial strain was detected by qualitative cup plate assay and tentatively identified to be Bacillus subtilis sp. B1 based on 16S rDNA sequencing and by matching the key morphological, physiological, and biochemical characteristics. The cultivation of Bacillus subtilis sp. B1 in the suitable liquid medium resulted in the production of high levels of enzyme. The colloidal chitin, peptone, and K2HPO4 represented the best carbon, nitrogen, and phosphorus sources, respectively. Enzyme production by Bacillus subtilis sp. B1 was optimized by the Taguchi method. Our results demonstrated that inoculation amount and temperature of incubation were the most significant factors influencing chitinase production. From the tested values, the best pH/temperature was obtained at pH 4 and 40?C, with values specific activity of chitinase to be 324.56 U/mg and 259.70 U/mg, respectively. In addition, the study of the morphological alteration of chitin treated by enzyme, indicating a potential application of this enzyme in several industries.